Tongue forces and handgrip strength in normal individuals: association with swallowing (Clinics, 2015)
OBJECTIVES: To describe and correlate tongue force and grip strength measures and to verify the association of these measures with water swallowing in different age groups. METHOD: Tongue force was evaluated using the Iowa Oral Performance Instrument and grip strength using the Hand Grip in 90 normal individuals, who were divided into three groups: young (18-39 years old), adult (40-59 years old) and elderly (above 60 years old) individuals. The time and number of swallows required for the continuous ingestion of 200 ml of water were also measured. RESULTS: A reduction in tongue force and grip strength, as well as an increase in the time required to drink 200 ml of water, were observed with increasing participant age. There was no difference in the number of swallows among the three groups. A correlation was observed between reductions in tongue force and grip strength in the groups of young and elderly individuals. CONCLUSION: There were differences in the measures of tongue force in young, adult and elderly individuals. Greater variations within these differences were observed when repeated movements were performed; in addition, a decrease in strength was associated with an increase in age. The decrease in tongue force among the elderly was offset by the increase in time needed to swallow the liquid. There was an association between the measures of tongue force and grip strength in the different age groups. The results of this study can be applied clinically and may act as a basis for guidelines in healthy or vulnerable elderly populations.